The role and safety of UVA and UVB in UV-induced skin erythema - Yang, Jing-Wen; Fan, Guo-Biao; Tan, Fei; Kong, Hai-Mei; Liu, Qing; Zou, Ying; Tan, Yi-Mei (Frontiers in Medicine, 2023)
Background Different wavelengths of ultraviolet (UV) light cause skin damage through different mechanisms. Minimal erythema dose (MED) is usually used to clinically evaluate skin sensitivity to ultraviolet radiation by inducing skin erythema using ultraviolet B (UVB) or ultraviolet A (UVA) + UVB. Aims In this study, we detected changes in the blood flow at the MED erythema caused by UVB and UVA + UVB radiation through optical coherence tomography (OCT) to explain the role of different bands of ultraviolet rays in erythema induction. Methods Two MED irradiation areas on the subjects' back were irradiated with UVB alone or UVA + UVB (UVA: UVB = 8:1). The absolute energy of UVB remained the same in UVB and UVA+UVB. At 24 h after the irradiation, the changes in the blood flow in the MED area were detected using OCT. Results Compared with the blank control, the maximum blood flow depth, blood flow peak, and total blood flow of UVB-MED and UVA+UVB-MED were significantly increased. Notably, the maximum blood flow depth and blood flow peak of UVB-MED were higher than UVA+UVB-MED. There was no significant difference in total blood perfusion between UVA+UVB-MED and UVB-MED. Under the same UVB energy, the skin erythema caused by UVA + UVB was weaker than UVB alone. Conclusions The analysis of local blood flow by OCT showed that the peak and maximum depth of local blood flow caused by UVB alone were significantly higher than UVA + UVB.